Islamic accounting in the Digital Era (integration of Islamic values in the transformation of financial technology) - Rizkina Kusumawardani; Gunawan Aji (Journal of Creative Power and Ambition (JCPA), 2026)
The development of digital technology has brought very significant changes in various sectors of life, including in finance and accounting. The method used is Library research by reviewing various relevant scientific literature, such as books, journals, and related official documents. The results showed that Sharia accounting has distinctive characteristics that prioritize the principles of justice, honesty, trustworthiness, and compliance with the Prohibition of riba, gharar, and maysir, which must still be maintained in the digitization process. Technological developments such as fintech, blockchain, and artificial intelligence provide great opportunities to improve efficiency, transparency, and accountability, but also present challenges in the form of Human Resource readiness, regulation, and potential value deviations. Therefore, a synergy between technological innovation and Sharia values is needed so that Sharia accounting remains relevant, adaptive, and contributes to realizing a fair and sustainable financial system